1997
DOI: 10.3719/weed.42.suppl_10
|View full text |Cite
|
Sign up to set email alerts
|

S-2 Soil-Adsorption of Quinclorac in the Dynamic Paddy Water-Soil System

Abstract: INTRODUCTION Most of Solanaceae crops are very sensitive to quinclorac. The most sensitive tomato does not grow normal when it is grown with the irrigation water or soil containing quiclorac at 10 and 0 .1ppb, respectively. Because of this property quinclorac is not used in Korea and Japan inspite of excelllence of the herbicide for the transplanted and direct-seeded rice. Developer of this herbicide introduces

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…When the flow rate is too excessive to allow for equilibration, then any available oxygen could form Fe oxides as reported by Kwon et al 12) Since the system is not in equilibrium, the surface oxide, would eventually get reduced but reduction may be kinetically slow and therefore not proceed to completion. On the other hand, if the gas flow rate for the same gas composition is lowered and any non-equilibrium oxygen is given time to react with hydrogen to establish the equilibrium oxygen partial pressure, then there will be less/ no Fe-oxides formed in the first place.…”
Section: Non Equilibrium Oxidation In Annealingmentioning
confidence: 89%
See 1 more Smart Citation
“…When the flow rate is too excessive to allow for equilibration, then any available oxygen could form Fe oxides as reported by Kwon et al 12) Since the system is not in equilibrium, the surface oxide, would eventually get reduced but reduction may be kinetically slow and therefore not proceed to completion. On the other hand, if the gas flow rate for the same gas composition is lowered and any non-equilibrium oxygen is given time to react with hydrogen to establish the equilibrium oxygen partial pressure, then there will be less/ no Fe-oxides formed in the first place.…”
Section: Non Equilibrium Oxidation In Annealingmentioning
confidence: 89%
“…When flow rate is increased, it is possible that the Po 2 increased because non-equilibrated O 2 in initial supply gas could react with Fe on the surface and form Fe oxides. Kwon et al 12) reported that only Fe 3 O 4 formed on the surface of TRIP steels when gas flow exceeds 150 cm/min. and DP is higher than -30°C when annealing in a Ar-5%H 2 gas.…”
Section: )mentioning
confidence: 99%